Gibson's paradox II - Greg Hanssgen (Levy Economics Institute of Bard College, 2006)
The Gibson paradox,long observed by economists and named by John Maynard Keynes (1936),is a positive relationship between the interest rate and the price level. This paper explains the relationship by means of interest-rate, cost-push inflation.In the mode,spending is driven in part by changes in the rate of interest, and the central bank sets the interest rate using a policy rule based on the levels of output and inflation. The model shows that the cost-push effect of inflation, long known as Gibson's paradox, intensifies destabilizing forces and can be involved in the generation of cycles.
Keywords: E12; E32; E52; 330; Gibson's Paradox; Inflation; Monetary Policy Rules : Nonlinear Dynamics; Hopf Bifurcation